Gender Attitudes Across Generations in Contemporary Armenian Society (Comparative Analysis) - Maria Zaslavskaya; Victor Agadjanian (Banber Erevani Hamalsarani. Sots'iologia, 2022)
Contemporary gender norms and attitudes in Armenia have been shaped by a complex interplay of pre-Soviet traditional culture, the legacy of the Soviet socialist modernization project, and the post-Soviet spread of western ideas and values. The paper examines generational differences in gender norms and attitudes in Armenian society, by comparing three generational groups. The mixed-method analysis is based on quantitative and qualitative data, including the nationally-representative household-based Gender Barometer Survey conducted in 2014, as well as in-depth interviews and focus group discussions among members of different generational groups in Armenia during 2015-2020. The results of the factor analysis show considerable generational complexity in gender norms and attitudes. We find that the majority of Armenian society, regardless of gender and generation, strongly adheres to the core family values and the corresponding gendered family roles. At the same time, the analyses show that individuals who belong to the older generation, i.e., the generation whose socialization took place under Soviet rule, display the most conservative patriarchal gender attitudes. The middle generation, whose coming of age occurred during the period of the early radical post-Soviet transformation, demonstrate inconsistent gender attitudes: while adhering to conservative gender norms, they are also most dissatisfied with the state of gender equality and in some aspects, such as achievement of status and wealth, display considerable gender egalitarianism. Finally, the youngest generation generally subscribes to the most egalitarian attitudes, but this group is far from homogenous, demonstrating a sharp divide between urban dwellers, who are very egalitarian-minded, and rural ones, who are remarkably conservative. Notably, young women living in cities display by far the most egalitarian attitudes. Moreover, among men, the generation is not a significant predictor of the level of egalitarianism in gender attitudes, compared to education and area of residence (city/village). However, it has a more significant impact on women’s perception of the traditional gender scheme. We conclude with a discussion of the role of changes in gender norms and attitudes in a broader transformation of Armenian society.